Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am stuck on this question for homework:

"Using the fact that if $z = \cos\theta + i \sin\theta$, then $z^n + z^{-n} = 2\cos n\theta$. Show that $$\cos^3 \theta = \tfrac14(\cos3 \theta+3\cos\theta)."$$

Thank you for helping me answering this question.

share|cite|improve this question
First: you can explain why $\frac1{(\cos\,u+i\sin\,u)^3}=\cos\,3u-i\sin\,3u$, right? – J. M. Nov 8 '12 at 7:22
Welcome to math.SE: since you are new, I wanted to let you know a few things about the site. In order to get the best possible answers, it is helpful if you say in what context you encountered the problem, and what your thoughts on it are; this will prevent people from telling you things you already know, and help them give their answers at the right level. Also, many find the use of imperative ("Prove", "Solve", etc.) to be rude when asking for help; please consider rewriting your post. – Did Nov 8 '12 at 7:44
Hi, thank you for answering my question. To J.M: sorry but i cant explain that answer. To Harald Hanche-Olsen : I will do right now. To did: thank you for the advice. – Zoren Nov 8 '12 at 7:58
up vote 0 down vote accepted

Key concept is to apply the angle sum identity to show the desired relationship.

$\sin(x+y) = \sin(x)\cos(y)+\cos(x)\sin(b)$

$\implies \sin(2x) = \sin(x+x) = \sin(x)\cos(x)+\cos(x)\sin(x)$

$\implies \sin(2x) = 2 \sin(x)\cos(x)$

$\cos(x + y) = \cos(x)\cos(y) - \sin(a)\sin(b)$

$\implies \cos(2x) = \cos(x+x) = \cos(x)^2 - \sin(x)^2$

$\implies \cos(3x) = \cos(1x + 2x) = \cos(2x)\cos(x) - \sin(x)\sin(2x)$

$\implies \cos(3x) = (\cos(x)^2 - \sin(x)^2)\cos(x) - \sin(x)(2 \sin(x)\cos(x))$

$\implies \cos(3x) = \cos(x)^3 - \sin(x)^2\cos(x) - 2\sin^2(x) \cos(x) $

$\implies \cos(3x) = \cos(x)^3 - 3\sin^2(x) \cos(x)$

$\implies \cos(x)^3 = \cos(3x) + 3\sin^2(x) \cos(x)$

$\sin^2(x) + \cos^2(x) = 1$

$\implies \sin^2 = 1 - \cos^2(x)$

$\implies \cos(x)^3 = \cos(3x) + 3 (1 - \cos^2(x)) \cos(x)$

$\implies \cos(x)^3 = \cos(3x) + 3\cos(x) - 3\cos^3(x) $

$\implies 4 \cos(x)^3 = \cos(3x) + 3\cos(x)$

$\implies \cos(x)^3 = \frac{1}{4} (\cos(3x) + 3\cos(x))$

share|cite|improve this answer
Hi lewellen, thank you very much for helping with this question. But is there another way in doing it by using the properties z=cosθ+isinθ and z^n+z^−n=2cosnθ? – Zoren Nov 8 '12 at 8:19

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.